Community-acquired Covid-19 Cluster among Non-Clinical Staff in a Teaching Hospital, Malaysia - Aizuddin, Azimatun Noor; Hod, Rozita; Hassan, Mohd Rohaizat; Ahmad, Norfazilah; Mohamed Nawi, Azmawati; Daud, Faiz; Arifin, Mohd Afiq (IIUM Medical Journal Malaysia, 2022)
A novel coronavirus, COVID-19 is responsible for the current outbreak of pneumonia. As of 16 September 2021, a total of 2,049,750 COVID-19 cases were recorded in Malaysia. In this study, we aimed to describe a cluster of COVID-19 cases among non-clinical staff in a teaching hospital in Kuala Lumpur Malaysia. We obtained epidemiological and clinical data from patients with confirmed COVID-19, via phone interviews and patient medical records. We performed chronological mapping of the cases to identify the possible period, mode of transmission, and cluster pattern. Three laboratory-confirmed COVID-19 cases were identified from the teaching hospital cluster. These three cases were linked epidemiologically to the religious gathering cluster in Malaysia. Seventy-four close contacts consisting of teaching hospital staff were quarantined. The median incubation period was four days (IQR 1-7). The need for intensified surveillance and a high level of alertness is vital to minimise the risk of widespread transmission in Malaysia.